Assessing Human Resource Competencies in Port Quarantine Supervision: An Analysis from Gorontalo, Indonesia - Kapiso, Pian; Tahir, Arifin; Aneta, Yanti; Abdussamad, Jurico (Journal Public Policy, 2025)
This study analyzes the resource advantages in health quarantine supervision at the Class II Gorontalo Port Health Office (KKP). Employing a descriptive qualitative approach, it investigates the fundamental contributions of officer knowledge, skills, and attitudes toward achieving operational success, maintaining public trust, and ensuring compliance with quarantine procedures. The findings reveal that KKP officers possess significant resource advantages. The officers' medical and epidemiological knowledge was found to be excellent, providing a critical foundation for the early detection of and response to potential infectious diseases. Furthermore, their technical and managerial skills proved highly competent in conducting health inspections, managing quarantine protocols, and effectively coordinating emergency responses. Moreover, the officers' professional, empathetic, and communicative attitudes were deemed optimal, playing a vital role in creating a positive experience for travelers, strengthening team collaboration, and enhancing community engagement. The study concludes that these resource advantages constitute a strategic asset for ensuring public health and safety within the port environment. Therefore, sustained investment in human resources through targeted training programs and supportive policy development is identified as key to maintaining and enhancing the long-term effectiveness of quarantine supervision.